The development of the ethmoidal region of Ascaphus truei (Stejneger) - Baard, E. H. W. (Ernst Hendrik Wolfaardt) (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MSc)--University of Stellenbosch, 1982.